Head to head comparison of intact and C-terminal fibroblast growth factor 23 in heart failure patients with reduced ejection fraction. (1st December 2017) - Gruson, Damien; Ferracin, Benjamin; Ahn, Sylvie A.; Rousseau, Michel F.
Highlights: FGF-23 regulates phosphorus homeostasis. FGF-23 elicits several direct effects on cardiac function and stimulates cardiomyocytes. FGF-23 participates to the course of heart failure. We compared intact and C-terminal FGF-23 in HFrEF patients. iFGF-23 appears as a stronger predictor for long-term cardiovascular death in HF patients.